Breaking away from Capital? Theorising activity in the shadow of Marx - Jones, Peter (Outlines. Critical Practice Studies, 2009)
The paper reflects on the relationship between the understanding of human activity which Marx expresses in Capital and the theoretical model of activity offered by an influential contemporary variant of Activity Theory. The paper argues that this variant departs significantly from Marx’s conception of human activity and its role in what he calls the ‘labour process’. In particular, Activity Theory has failed to distinguish between the labour process and the valorization process, a distinction which is fundamental to Capital and to Marx’s theoretical and political perspective more generally. The paper also argues that this conceptual conflation is also evident in the theoretical discourse of the founders of the Activity Theory tradition. The paper goes on to consider the theoretical and practical implications of this departure from the method and conclusions of Capital.